The Effect of Leverage, Company Size and Bond Age on Bond Ratings in the Financial Sector on the Indonesia Stock Exchange (IDX) - Nurpadila Nurpadila; Djamaluddin Kadir; Kodding Haseng (International Journal of Artificial Intelligence Research, 2022)
This study aims to examine the effect of Leverage, Company Size and Bond Age on Bond Ratings in financial sector companies on the Indonesia Stock Exchange (IDX). Based on the research results previously described, the following conclusions can be drawn: (1) Leverage has no significant effect on bond ratings. Based on these results, it shows that the first hypothesis is rejected. (2) Company size has a significant effect on bond ratings. Based on these results, it shows that the second hypothesis is accepted. (3) Bond Age has a significant effect on bond ratings. Based on these results, it shows that the third hypothesis is accepted.